2011
DOI: 10.1111/j.1467-9507.2011.00633.x
|View full text |Cite
|
Sign up to set email alerts
|

Romantic Relationship Commitment and Its Linkages with Commitment to Parents and Friends during Adolescence

Abstract: This five-wave longitudinal study examines linkages between adolescents' perceptions of romantic relationship commitment and the development of adolescents' perceptions of commitment to parents and friends. A total of 218 early-to-middle adolescents (39.0 percent boys) and 185 middle-to-late adolescents (30.8 percent boys) participated.Multivariate growth curves showed that higher base levels of commitment and a stronger positive development of commitment to parents and friends were associated with higher leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
32
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 38 publications
4
32
0
3
Order By: Relevance
“…Low-quality parental bonds provide limited opportunities for youth to practice important interpersonal skills (e.g., listening, empathy, conflict resolution). Longitudinal evidence supports the link between parental relationships and future relationships (e.g., [13,14]); for example, Johnson and Galambos (2014) found a positive association between parent-adolescent relationship quality and romantic relationship quality in young adulthood [15]. Given associations between parent-adolescent relationship quality and both pubertal timing and later romantic relationship quality, we investigate whether parent-adolescent relationship quality mediates any identified link between pubertal timing and later romantic relationships.…”
mentioning
confidence: 98%
“…Low-quality parental bonds provide limited opportunities for youth to practice important interpersonal skills (e.g., listening, empathy, conflict resolution). Longitudinal evidence supports the link between parental relationships and future relationships (e.g., [13,14]); for example, Johnson and Galambos (2014) found a positive association between parent-adolescent relationship quality and romantic relationship quality in young adulthood [15]. Given associations between parent-adolescent relationship quality and both pubertal timing and later romantic relationship quality, we investigate whether parent-adolescent relationship quality mediates any identified link between pubertal timing and later romantic relationships.…”
mentioning
confidence: 98%
“…Our results call for future studies about the specific contribution of romantic experiences to identity formation among other forms of relational experiences, such as parents and friends, which already have interdependent contributions (De Goede et al, ). As suggested by Beyers and Seiffge‐Krenke (), identity is known to develop in a web of intimate relationships, not only in romance.…”
Section: Discussionmentioning
confidence: 71%
“…Empirical studies indicate that adolescents spend time on activities related to romance such as thinking about a current or desired lover, chatting about this topic with peers or interacting with a romantic partner (Furman & Collins, ). To date, most studies have focused on adolescents' current involvement in romantic relationships to explore their characteristics and their contribution to development (e.g., De Goede, Branje, van Duin, VanderValk, & Meeus, ; Kerpelman et al, ). However, longitudinal studies about romantic involvement and the duration of relationships revealed that a significant proportion of adolescents, even in their late teens, are not involved in either steady or casual romantic relationships (Boisvert & Poulin, ; Rauer, Pettit, Lansford, Bates, & Dodge, ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings from other studies showed that caring and communication were associated with intimacy and supportiveness. 10,30,31 Much of the literature on partner selection 3235 and relationship quality 1,10,36,37 focus on older adolescents and adolescent mothers. More research involving early adolescents is needed.…”
Section: Discussionmentioning
confidence: 99%